Analisis Permintaan dan Elastisitas Daging Sapi pada Tingkat Rumah Tangga - Muhammad Chalidin; Zulkarnain Lubis; Mitra Musika Lubis (Jurnal Ilmiah Pertanian ( JIPERTA), 2019)
This study aims to determine the level of beef demand, the factors that affect beef demand and measure and identify the role of the elasticity of factors that affect beef demand. Sampling is done by simple random sampling. The data analysis method used is qualitative (descriptive) and quantitative analysis. The results showed that the demand for beef at the household level in Sei Sikambing B village, the average beef consumption was 2.2 kg / month. Simultaneously the test results show that the variable beef prices, fish prices, chicken meat prices, egg prices, the level of household income, the number of family members, and taste have a real impact on the amount of beef demand at a 95% confidence level. On the price of partial fish, the price of chicken cuts, the level of household income and tastes significantly influence the demand for beef at a 95% confidence level, while the variable beef prices, egg prices, and the number of family members do not significantly influence the demand for beef meat at the level 95% confidence. From the estimation that the determination value (R2) of 67.8% variation of the seven variables can explain the amount of beef demand, while the remaining 32.2% is influenced by other variables. Beef demand is not elastic to changes in beef prices.Keywords: Demand, Elasticity, Price, Beef, Income